Eight-year follow-up of a randomized clinical trial comparing ultrasound-guided foam sclerotherapy with surgical stripping of the great saphenous vein. Issue 6 (13th April 2018) - Lam, Y L; Lawson, J A; Toonder, I M; Shadid, N H; Sommer, A; Veenstra, M; van der Kleij, A M J; Ceulen, R P; de Haan, E; Ibrahim, F; van Dooren, T; Nieman, F H; et al.
Abstract: Background: This was an 8-year follow-up of an RCT comparing ultrasound-guided foam sclerotherapy (UGFS) with high ligation and surgical stripping (HL/S) of the great saphenous vein (GSV). Methods: Patients were randomized to UGFS or HL/S of the GSV. The primary outcome was the recurrence of symptomatic GSV reflux. Secondary outcomes were patterns of reflux according to recurrent varices after surgery, Clinical Etiologic Anatomic Pathophysiologic (CEAP) classification, Venous Clinical Severity Score (VCSS) and EuroQol Five Dimensions (EQ-5D™) quality-of-life scores. Results: Of 430 patients originally randomized (230 UGFS, 200 HL/S), 227 (52·8 per cent; 123 UGFS, 103 HL/S) were available for analysis after 8 years. The proportion of patients free from symptomatic GSV reflux at 8 years was lower after UGFS than HL/S (55·1 versus 72·1 per cent; P = 0·024). The rate of absence of GSV reflux, irrespective of venous symptoms, at 8 years was 33·1 and 49·7 per cent respectively ( P = 0·009). More saphenofemoral junction (SFJ) failure (65·8 versus 41·7 per cent; P = 0·001) and recurrent reflux in the above-knee GSV (72·5 versus 20·4 per cent; P = 0·001) was evident in the UGFS group. The VCSS was worse than preoperative scores in both groups after 8 years; CEAP classification and EQ-5D® scores were similar in the two groups. Conclusion: Surgical stripping had a technically better outcome in terms of recurrence of GSV and SFJ reflux than UGFS in the long term. Long-term follow-up suggests significant clinical progression of venous disease measured by VCSS in both groups, but less after surgery. Registration number: NCT02304146 (http://www.clinicaltrials.gov ). Abstract : Surgery better